2008
DOI: 10.1016/j.jbiomech.2007.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the effect of cross-shear on the wear of conventional and highly cross-linked UHMWPE

Abstract: A computational model has been developed to quantify the degree of cross-shear of a polyethylene pin articulating against a metallic plate, based on the direct simulation of a multidirectional pin-onplate wear machine. The principal molecular orientation (PMO) was determined for each polymer site. The frictional work in the direction perpendicular to the PMO was assumed to produce the greatest orientation softening (Wang et al., 1997). The cross-shear ratio (CS) was defined as the frictional work perpendicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
168
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(175 citation statements)
references
References 19 publications
7
168
0
Order By: Relevance
“…Reduced cross shear ratio reduced the wear factor in the pin-on-plate studies for the two different stress levels studied [13,20] (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Reduced cross shear ratio reduced the wear factor in the pin-on-plate studies for the two different stress levels studied [13,20] (Fig. 1).…”
Section: Resultsmentioning
confidence: 92%
“…The rapid decrease in the wear factor as the cross shear ratio decreased from 0.1 to 0 is of particular note. The experimental data were curved fitted over the cross shear range 0 to 0.25, and the logarithmic curve [20] extrapolated to cover the full range of cross shear possible up to 0.5. These results also indicated that the values of the wear factor were dependent on the contact conditions, the load, contact area, and stress level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 50% lower wear rate of the TKR inserts compared with the THR liners for regular wear (no delamination) may be a result of the lower degree of multidirectional motion in the knee [18,31]. This comparison entailed adjusting the wear rates to a patient age of 70 years to account for age dependence, and included only active patients.…”
Section: Discussionmentioning
confidence: 99%